Investigation of the influences of wetting layer, size and shape of quantum dots on the energy states in INAS/GAAS semiconductor quantum dots - Gu, Zhenming. (2013)
The influences of wetting layer, size and shape of quantum dots on the conduction band of the electron from InAs/GaAs semiconductor quantum dots are studied theoretically and numerically. Models are constructed into conical, spherical and cylindrical shapes of quantum dots with different sizes. Furthermore, models are also subjected to the cases for the presence or absence of a thin wetting layer with few monolayer InAs. The results are emerged in the simple one-band Schrödinger equation in the effective mass approximation. The formulation of the models also takes considerations to the boundary conditions for the entire structure due to this approximation. The numerical results demonstrate the influences of these three variables on the quantum confinement effect of electrons in the conduction band. In order to analyze these outcomes, the wave functions and eigenvalues of different models are plotted and discussed majorly at the ground state and the first excited state. The demonstrations explain the significance of the wetting layer on the quantum properties of the small quantum dots, and large conical quantum dot with a uniform wetting layer of 2nm thickness is found to have the best strength in quantum confinement. In reality, majority of these quantum dots can be utilized in electronic, optoelectronic and photogalvanic areas with dependence of their own quantum confinement properties.